EMERGING AND RE-EMERGING BACTERIAL ZOONOSES SCREENING OF HIGH RISK GROUPS FOR LEPTOSPIRAL SEROVARS - Clitus, A; Anupriya, A; PRABHUSARAN, N (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: To collect information related to leptospirosis among high-risk groups: agricultural workers, butchers, construction workers, and hospital sanitary workers through questionnaires and to determine the presence of leptospires among these high-risk groups (both genus and serovarspecific). Methods: A total of 367 eligible subjects were included (112 agricultural workers, 108 construction site workers, 89 sanitary workers, and 58 butchers). Results: The genus-specific enzyme-linked immunosorbent assay was performed for all the serum samples (n=367) and showed reactiveness among 149 subjects. The results were compared with the serovar-specific microscopic agglutination test, which showed positivity in 158 subjects. Conclusion: Screening the occupational risk group for the presence of leptopsiral prints in order to provide appropriate medical check-ups and the earliest treatment. An educational program for rodent control and infection control where the seroprevalence is high should be organized.